Pengukuran modal intelektual dengan metode kapitalisasi pasar - Rosemarie Sutjiati Njotoprajitno; Friska Tambunan (Jurnal Manajemen Maranatha, 2019)
In order to generate company’s income, assets are needed either as input of production process or for other usage. One type of assets is intelectual capital. Many experts in business state the increasing importance of intelectual capital in nowadays business. This research tries to examine intelectual capital value using market capitalization method. This research also tries to examine the effect of intelectual capital to generate profit in a company. This research uses quantitative method by using simple linear regression method to test the effect of intelectual capital to profit. Intelectual capital value is calculated using market capitalization method or market value to book value (MVBV) while company’s profit is calculated by return on equity (ROE). The examined companies are from consumer goods companies listed in Indonesia Stock Exchange from 2014 to 2017 that have completed data and generated positive MVBV and ROE. The result shows that Intelectual capital has positive and signficant effect to ROE.